1997
DOI: 10.1021/jp9714835
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Porous Aggregates of the Ammonium Salt of Dodecatungstophosphoric Acid, (NH4)3PW12O40:  Unidirectionally Oriented Self-Assembly of Nanocrystallites

Abstract: It was demonstrated that porous aggregates of (NH4)3PW12O40 nanocrystallites were formed by epitaxial self-assembly, when dodecatungstophosphoric acid was precipitated by ammonium hydrogen carbonate in an aqueous solution. Scanning electron microscopy combined with nitrogen and argon adsorption measurements showed that nanocrystallites of (NH4)3PW12O40 formed aggregates of ca. 0.3−1 μm in size, which are porous with a nearly uniform micropore size of 0.6−1.3 nm in diameter. The shape of these aggregates change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 26 publications
(48 reference statements)
2
59
0
2
Order By: Relevance
“…The XRD patterns of (NH 4 ) 3 PW 12 O 40 /SiO 2 having W/Si molar ratio of 2/8 revealed that the Keggin structure of (NH 4 ) 3 PW 12 O 40 was maintained which was calcined at 450°C or less. The XRD pattern of (NH 4 ) 3-PW 12 O 40 /SiO 2 is consistent to that of (NH 4 ) 3 PW 12 O 40 in the reported papers [22,23]. Izumi et al have reported that (NH 4 ) 3 PW 12 O 40 was converted to (NH 4 ) 2-HPW 12 O 40 when it was heated at 450°C for 2 h, which was determined by thermogravimetric analysis [24].…”
Section: Resultssupporting
confidence: 81%
“…The XRD patterns of (NH 4 ) 3 PW 12 O 40 /SiO 2 having W/Si molar ratio of 2/8 revealed that the Keggin structure of (NH 4 ) 3 PW 12 O 40 was maintained which was calcined at 450°C or less. The XRD pattern of (NH 4 ) 3-PW 12 O 40 /SiO 2 is consistent to that of (NH 4 ) 3 PW 12 O 40 in the reported papers [22,23]. Izumi et al have reported that (NH 4 ) 3 PW 12 O 40 was converted to (NH 4 ) 2-HPW 12 O 40 when it was heated at 450°C for 2 h, which was determined by thermogravimetric analysis [24].…”
Section: Resultssupporting
confidence: 81%
“…[76][77][78] Self-organization seems to allow control even at the supramolecular scale. [46,79,80] In situ studies cast considerable doubt, however, on the allegation that these solids are active in their as-prepared form; their surfacse seem to exhibit differences from the crystalline bulk, and hence a detailed understanding of their structural dynamics is required to control the genesis and stability of the active sites. [81,82] Another strategy is to reduce the size of the active site to a very small number of atoms to prepare "single-site" catalysts, which offer the chance to exactly control the active site and its environment on the molecular scale.…”
Section: Alternative Routes To Controlled Synthesismentioning
confidence: 99%
“…Moreover, necks between the crystallites were found to grow epitaxially during the formation process, enabling the nanocrystallites to form strong connection with each other; a phenomenon we defined as ''Epitaxial Self Assembly'' [17][18][19][20][21][22][23], as shown in figure 1. In this non-classical crystallization mechanism, the nanocrystallites form in supersaturated solutions, aggregating in an ordered manner, gaining higher crystallinity in the process.…”
Section: Introductionmentioning
confidence: 99%